Collective Research Review on Chaotic Based Encryption Algorithms, Speech Encryption Algorithms and Cryptographic Requirements - Pushpalatha G S; Dr. Ramesh S (International Journal of Engineering and Management Research, 2024)
Chaotic cryptography has been a recent development by researchers due to its interesting properties such as non-linear behavior, sensitivity to initial conditions, ergodicity, mixing, confusion and diffusion etc. This paper is a brief review of various standard encryption algorithms, cryptographic requirements for design of chaotic based cryptosystem and chaos-based speech encryption algorithms. This study also gives various statistical tests needs to be considered for conformity about suitable randomness of the binary sequences generated using either hardware or software means for cryptographic applications as key sequence.